Mean Platelet Volume and the Ratio of Mean Platelet Volume/Platelet Count in Acute Rheumatic Fever - Dolunay Gürses; Funda Akpınar; Mustafa Doğan (Galenos Yayinevi, 2021)
Aim:Acute rheumatic fever (ARF) is an endemic disease especially in developing countries. Due to an autoimmune response to group B streptococcus throat infection, ARF develops in susceptible children. Mean platelet volume (MPV) reflects the platelet size and the rate of platelet production. It is important in cardiovascular events and rheumatic diseases. The MPV/platelet count ratio was determined to be more sensitive than MPV alone in patients with hepatocellular carcinoma, deep vein thrombosis and myocardial infarction. The aim of this study was to investigate changes in MPV and the MPV/platelet count ratio during the active and remission periods of ARF compared with healthy subjects.Materials and Methods:This study population consisted with 70 ARF patients and 70 age and gender matched healthy controls. In all subjects, complete blood count; including haemoglobin, white blood cell count (WBC), platelet count, MPV and C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) were measured during the active stage and during the remission period and compared with healthy individuals.Results:There was no statistically significant difference between the ARF and control groups in terms of the sex and age (p>0.05). Forty-one patients in the ARF group had carditis. The ARF patients in the active stage had significantly higher WBC, CRP and ESR values (p<0.05). Although no significant difference was observed in MPV between the groups (p>0.05); the MPV/platelet count ratio was low during the active stage but increased during the remission period and reached the same values as the healthy controls (p<0.001).Conclusion:We did not find any relationship between MPV and ARF. However, a decreased MPV/platelet count ratio was detected during the active stage of ARF. The present findings emphasize the association between the MPV/platelet count ratio and ARF. The MPV/platelet count ratio may be used to determine the activity of ARF.